Adjusted COVID-19 booster schedules balance age-dependent differences in antibody titers benefitting risk populations - Müller, Lisa; Andrée, Marcel; Moskorz, Wiebke; Drexler, Ingo; Hauka, Sandra; Ptok, Johannes; Walotka, Lara; Grothmann, Ramona; Hillebrandt, Jonas; Ritchie, Anastasia; Peter, Laura; Walker, Andreas; et al. (Frontiers in Aging, 2022)
We provide follow-up data on the humoral immune response after COVID-19 vaccinations of two distinct cohorts aged below 60 and over 80 years to screen for age-related differences in the longevity and magnitude of the induction of the antibody responses post booster-vaccinations. While anti-SARS-CoV-2 spike-specific IgG and neutralization capacity waned rapidly after the initial vaccination schedule, additional boosters highly benefitted the humoral immune responses especially in the elderly cohort, including the neutralization of Omikron variants. Thus, adjusted COVID-19 booster vaccination schedules are an appropriate tool to overcome limitations in the success of vaccinations.